2020
DOI: 10.1155/2020/7291075
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin Ameliorates Renal Interstitial Fibrosis via Regulating TGF‐β1/Smad and NF‐κB Signaling in UUO Rat Model

Abstract: Purpose. Hirudin, a polypeptide structure containing 65 amino acids, is a potent natural thrombin inhibitor with anticoagulant property extracted from Hirudo medicinalis. It has been reported to have anti-inflammatory and antifibrotic property. Here we explored the renoprotective effect of hirudin on unilateral ureteral obstruction (UUO) induced renal interstitial fibrosis (RIF). Methods. Rats were randomly divided into five groups: sham group, UUO alone group, and three UUO + hirudin-treatment groups (10, 20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Other in vitro studies showed that the natural PAR-1 ligand, thrombin, provoked a time- and concentration-dependent IL-6 release in endothelial cells [ 58 ]. The application of hirudin, a natural thrombin inhibitor, resulted in a reduced expression of both PAR-1 and IL-6, as well as decreased accumulation of ECM in the renal interstitium [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro studies showed that the natural PAR-1 ligand, thrombin, provoked a time- and concentration-dependent IL-6 release in endothelial cells [ 58 ]. The application of hirudin, a natural thrombin inhibitor, resulted in a reduced expression of both PAR-1 and IL-6, as well as decreased accumulation of ECM in the renal interstitium [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blocking TGF-β 1 signaling pathway may be an effective strategy for fibrosis, such as RIF. Recently, Yang et al confirmed that hirudin (10, 20, 40 IU/kg) could alleviate the renal damage and the deposition of ECM in renal interstitium of unilateral ureteral obstruction (UUO) rats (Yang et al, 2020). The expressions of TGF-β 1 , phosphorylated-Smad2, and phosphorylated-Smad3 in the kidneys of UUO rats were decreased, which illustrated the inhibition of TGF-β 1 /Smad signaling.…”
Section: Tgf-β 1 /Smad/nf-κbmentioning
confidence: 94%
“…The corresponding drug was given to each group of rats on the same day after the operation. The dose of the drug administered was determined according to the animal/human surface area method of conversion and combined with the results of the previous experiments ( Yang K. et al, 2020 ). UUO hirudin treatment group with a dose of 40 IU/kg/d by tail vein injection, and the UUO group as well as Sham group with stroke-physiological saline solution (SPSS) by tail vein injection too.…”
Section: Methodsmentioning
confidence: 99%